2016
DOI: 10.1111/jzs.12116
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the number of molecular markers resolves the phylogenetic relationship of ‘Cepaeavindobonensis (Pfeiffer 1828) with Caucasotachea Boettger 1909 (Gastropoda: Pulmonata: Helicidae)

Abstract: ‘Cepaea’ vindobonensis has been shown to be closely related to Caucasotachea in recent molecular studies. The phylogenetic relationships within this clade and especially the phylogenetic position of ‘Cepaea’ vindobonensis were, however, not well resolved. Our phylogenetic analyses on the basis of an increased number of molecular genetic loci from the mitochondrial and nuclear genomes unambiguously demonstrate that ‘Cepaea’ vindobonensis represents the sister group of the Caucasotachea taxa, with C. leucoranea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
9
0
1
Order By: Relevance
“…This point of view has now completely changed because molecular phylogenetic evidence has rejected the monophyly of former Cepaea (Neiber and Hausdorf 2015), instead placing C. vindobonensis into Caucasotachea. As all other members of Caucasotachea are distributed in the Caucasian mountains and along the coasts of the eastern Black Sea and western Caspian Sea (Neiber and Hausdorf 2015; Neiber et al 2016), it is likely that the group originated in that region. Oldest (Middle Miocene) fossil records conchologically resembling modern C. vindobonensis are from Crimea (Egorov, unpublished data), which provide further support for this assumption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This point of view has now completely changed because molecular phylogenetic evidence has rejected the monophyly of former Cepaea (Neiber and Hausdorf 2015), instead placing C. vindobonensis into Caucasotachea. As all other members of Caucasotachea are distributed in the Caucasian mountains and along the coasts of the eastern Black Sea and western Caspian Sea (Neiber and Hausdorf 2015; Neiber et al 2016), it is likely that the group originated in that region. Oldest (Middle Miocene) fossil records conchologically resembling modern C. vindobonensis are from Crimea (Egorov, unpublished data), which provide further support for this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the distribution and local frequency, the snail is believed to be a predominantly central-eastern European species (Ložek 1964). Although it was long classified within the genus Cepaea Held, 1838 (Kerney et al 1983), recent molecular evidence has shown that the species should better be placed in the genus Caucasotachea (Neiber and Hausdorf 2015; Neiber et al 2016). As all other Caucasotachea species are distributed around the Caucasus and Mt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Наши исследования в основном проводились на южном макросклоне Среднерусской возвышен-ности (Белгородская и Харьковская области), где проходит северо-восточная граница естественного ареала этого вида. На данной территории улитки оби-тают в реликтовых сообществах доледникового и послеледникового перио-дов, таких как меловые боры и нагорные дубравы, а также они встречаются 1 В ряде работ по молекулярной таксономии данный вид относят к роду Caucasotachea [16,17]. …”
unclassified
“…Additionally, partial sequences of the nuclear ribosomal RNA‐coding cluster were amplified: (i) a fragment of the 5′ end of the 18S rRNA gene and (ii) a fragment spanning the 3′ end of the 18S rRNA gene, the complete internal transcribed spacer 1 (ITS1), the complete 5.8S rRNA gene, the complete ITS2 and the 5′ end of the 28S rRNA gene. The first fragment was amplified using the primer pair SWAM_18SF and SWAM_18SR (Attwood et al., ) and the second fragment was assembled from overlapping fragments that were amplified using the primer pairs 18S2093 (Neiber et al., ) plus 5.8S_MNR1 (this study), LSU1 plus LSU3 (Wade and Mordan, ), LSU 2 plus LSU4 (Wade and Mordan, ), 28S_2F plus 28S_1145R (Uit de Weerd, ) and 28S_1128F plus 28S_2119R (Uit de Weerd, ), respectively. For information on primers, see Table .…”
Section: Methodsmentioning
confidence: 99%